Coastal fishes of Rio Grande do Norte, northeastern Brazil, with new records - José Garcia Júnior; Marcelo Nóbrega; Jorge Oliveira (Check List, 2015)
An updated and reviewed checklist of coastal fishes of the Rio Grande do Norte state, northeastern coast of Brazil, is presented. Between 2003 and 2013 the occurrence of fish species were recorded through collection of specimens, landing records of the artisanal fleet, literature reviews and from specimens deposited in ichthyological collections. A total of 459 species from 2 classes, 26 orders, 102 families and 264 genera is listed, with 83 species (18% of the total number) recorded for the first time in the study area. Additionally, Halichoeres radiatus, Lachnolaimus maximus and Canthigaster jamestyleri are reported for the first time in the Brazilian coast and nine other species have their geographic distribution extended.